Devil in The Digital: Ambivalent Results in an Object‐Based Teaching Course. (September 2015) - Turin, Mark
Abstract In 2013, I piloted a course in which students used Web‐based tools to explore underdocumented collections of Himalayan materials at Yale University. Through class‐based research and contextualization, I set students the goal of augmenting existing metadata and designing media‐rich, virtual tours of the collections that could be incorporated into the sparse catalogue holdings held within the library system. The process was experimental and had mixed results, as this article documents. The class provided an opportunity for undergraduate students from any discipline to work with objects and primary materials, requiring them to evaluate different sources of information, value, and legitimacy. Learning outcomes were nontraditional and intentionally underscripted. The collaborative and hands‐on approaches toward digitization that de‐emphasized the authority of the instructor were unsettling to some students. [digital humanities, mobile classroom, critical pedagogy, material culture, Himalaya]